2019
DOI: 10.3390/rel10070420
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel as Though I’m Doing the Job of the Imam for Them”: Considering ‘Tactical’ Muslim Leadership Through the Case of ‘Muslim RE Teachers’

Abstract: Although Muslim leadership in Britain has long been the focus of scholarly attention, discussion has tended to prioritise “official” Muslim leaders (Birt 2006; Geaves 2008; Ahmad and Evergeti 2010). However, what constitutes a “Muslim leader” is increasingly contested, revealing instead a diversity of authoritative ‘claim makers’ and representative positions (Jones et al. 2015). These contestations were a recurring theme throughout the Leadership, Authority and Representation in British Muslim Communities conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Moving beyond the usual spaces of mosques, churches and temples, scholars have found ample fertile ground in locating religious practice at alternative sites such as museums (Kong, 2005;Buggein, 2012;McCormack, 2017), schools (Kong, 2005;Bobrowicz, 2018;Vince, 2019), development and humanitarian NGOs (Beaumont, 2008;Clarke and Jennings, 2008;Ngo, 2018); roadside shrines (Preston, 2002;Solso, 2015;Osterberg, 2018), media spaces ( Vásquez and Marquardt, 2000;Kong, 2006;De Wildt et al, 2018 ), streetscapes (Ismail, 2006;Jones, 2006), sites of financial practice Samers, 2007, 2013;Bassens et al, 2013) and home spaces (Kong, 2002;Tweed, 2006). A further site of difference recognised by geographers of religion has been embodied experiences of the sacred -drawing attention to emotion and affect.…”
Section: Approaching Religion Relationallymentioning
confidence: 99%
“…Moving beyond the usual spaces of mosques, churches and temples, scholars have found ample fertile ground in locating religious practice at alternative sites such as museums (Kong, 2005;Buggein, 2012;McCormack, 2017), schools (Kong, 2005;Bobrowicz, 2018;Vince, 2019), development and humanitarian NGOs (Beaumont, 2008;Clarke and Jennings, 2008;Ngo, 2018); roadside shrines (Preston, 2002;Solso, 2015;Osterberg, 2018), media spaces ( Vásquez and Marquardt, 2000;Kong, 2006;De Wildt et al, 2018 ), streetscapes (Ismail, 2006;Jones, 2006), sites of financial practice Samers, 2007, 2013;Bassens et al, 2013) and home spaces (Kong, 2002;Tweed, 2006). A further site of difference recognised by geographers of religion has been embodied experiences of the sacred -drawing attention to emotion and affect.…”
Section: Approaching Religion Relationallymentioning
confidence: 99%
“…It has been shown that groups like Daesh employ an out-of-context theological narrative that is proving to be very influential, especially among the young (Mansouri and Keskin 2019). In this vein, Islamic religion teachers can be presented as role models for their students (Vince 2019), helping them to acquire the necessary skills and capabilities for recognising terrorist propaganda (Brooks and Ezzani 2017).…”
Section: Introductionmentioning
confidence: 99%